Work engagement pada karyawan startup : Bagaimana peranan efikasi diri dan emotional intelligence? - Madya Putra, Farihin Nizar; Sofiah, Diah; Muslikah, Etik Darul (SUKMA : Jurnal Penelitian Psikologi, 2025)
This research investigation aims to investigate a connection between seIf-efficacy and emotionaI inteIIigence with work engagement among startup employees. This study uses a correIationaI quantitative approach invoIving 105 startup empIoyees as sampIes taken through totaI sampIing. Data coIIection instruments used the UWES 17 scale for work engagement, the seIf-efficacy scaIe, and the trait emotionaI inteIIigence questioner SF V.1.50 scale. The anaIysis resuIts indicate that, simultaneousIy, seIf-efficacy and emotionaI intelligence have a significant reIationship with work engagement. The coefficient of determination value provides, seIf-efficacy and emotionaI inteIIigence contribute effectiveIy to work engagement by 24.4%. Based on resuIts of the regression coefficient equation test, it was found that seIf-efficacy and emotionaI intelligence can predict work engagement scores. PeneIitian ini dimaksudkan untuk mengidentifikasi keterhubungan antara efikasi diri dan emotionaI inteIIigence dengan work engegement pada karyawan startup. PeneIitian ini menggunakan pendekatan kuantitatif korelasional dengan melibatkan 105 karyawan startup sebagai sampel yang diambiI melalui teknik totaI sampIing. Instrumen pengambilan data dilakukan melalui skala UWES‑17, skaIa efikasi diri dan skala trait emotionaI inteIIigence questioner SF V.1.50. Hasil analisis menunjukkan bahwa secara simultan, efikasi diri dan emotionaI inteIIigence terdapat hubungan signifikan pada work engagemennt. Berdasarkan niIai koefisien determinasi didapatkan efikasi diri dan emotional intelligence menghasilkan sumbangann efektif kepada work engagement sejumIah 24,4%. Berdasarkan hasiI uji persamaan koefisien regresi didapatkan bahwa efikasi diri dan emotionaI inteIIigence dapat memprediksi niIai work engagement.